Cardiac and Cerebral Arterial Complications of Lemierre Syndrome: Results from a Systematic Review and Individual Patient Data Meta-analysis - Pleming, William; Barco, Stefano; Voci, Davide; Sacco, Clara; Zane, Federica; Granziera, Serena; Corsi, Gabriele; Konstantinides, Stavros V.; Kucher, Nils; Pecci, Alessandro; Valerio, Luca (Hämostaseologie, 2022)
Background Lemierre syndrome is a potentially life-threatening disease, which affects otherwise healthy young adults and adolescents. It is characterized by acute neck vein thrombosis and septic embolism, usually complicating a bacterial infection. Data on the syndrome are sparse, particularly concerning arterial complications.Methods We evaluated the frequency and patterns of cerebral arterial and cardiac involvement (“arterial complications”) in an individual patient level cohort of 712 patients, representing all cases described over the past 20 years in the medical literature who fulfilled the criteria: (1) bacterial infection in the neck/head site and (2) objectively confirmed thrombotic complication or septic embolism. The study outcomes were defined as all-cause in-hospital deaths and the occurrence of clinical sequelae at discharge or in the postdischarge period.Results A total of 55 (7.7%) patients had an arterial complication. The most frequent arterial complications were carotid involvement (52.7%), stroke (38.2%), and pericardial complications (20%). Patients with an arterial involvement were more likely to be treated with a greater number of antibiotics (23 vs. 10%) and to receive anticoagulation. In addition, patients with arterial complications had a greater risk of all-cause death (n = 20/600, 3.3% vs. n = 6/52, 12%; odds ratio [OR]: 3.8; 95% confidence interval [CI]: 1.5–9.9) and late clinical sequelae (n = 49/580, 9.0% vs. n = 15/46, 35%; OR: 5.2; 95% CI: 2.65–10.37).Conclusions While Lemierre syndrome is known to be primarily characterized by venous thromboembolic events, our results suggest that local or distant arterial complications may occur in approximately one-tenth of patients and may be associated with a greater risk of long-term sequelae and death.
Keywords: Lemierre syndrome; thrombosis; stroke; septic embolism; anticoagulation; Fusobacterium necrophorum